Psychological maturity and psychological well-being in students of a Private Educational Institution in Juliaca - Peru - Mamani Sucto, Yesenia (2021)
Objective: To determine the relationship between psychological maturity and psychological well-beingin students of a Private Educational Institution in Juliaca. Methodology: A correlational study, witha non-experimental design and a cross-sectional section, applied to a population of 78 students ofboth sexes in the fourth and fifth grade of secondary education; to whom the Ryff Psychological Wellbeingscale and the Psychological Maturity questionnaire (PSYMAS) were applied. The survey wasconducted online and the analyzes considered a significance level of 5%. Results: 61.5% of thosesurveyed show a moderate level of psychological maturity, and 100% show well-being at a low level.Inferential analysis showed significant correlations between psychological maturity and psychologicalwell-being (Rho = .289, p <.05). Conclusion: To the extent that adolescents are psychologically mature,then, the more likely it is to have pleasant sensations throughout life or to satisfy personal desire.